Comparison of Modified Cartilage Shield Tympanoplasty with Tympanoplasty Using Temporalis Fascia Only: Retrospective Analysis of 142 Cases - Sohil Vadiya; Vibhuti Parikh; Saumya Shah; Parita Pandya; Anuj Kansara (Scientifica)
The current study compares outcomes of modified cartilage shield tympanoplasty (CST) with temporalis fascia tympanoplasty in type I procedures in Indian patients. Graft uptake rates are better with the CST technique and hearing results are almost equivalent with both techniques except at 8000 Hz where improvement in hearing was found better with the use of temporalis fascia alone. The CST technique used in the study is unique.